2015
DOI: 10.1080/23308249.2015.1024825
|View full text |Cite
|
Sign up to set email alerts
|

Rainbow Trout in Europe: Introduction, Naturalization, and Impacts

Abstract: The rainbow trout (Oncorhynchus mykiss) is probably the most widely introduced fish species in the world. Since the first translocation outside of the range of its natural distribution, the species has been introduced into at least 99 countries and has established reproducing populations in many different parts of the world. The present review aims to synthesize the existing information on these translocations, with special emphasis on self-sustaining populations in Europe, where continuous introductions have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
93
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(101 citation statements)
references
References 111 publications
0
93
0
Order By: Relevance
“…Despite the lack of data about fishing pressure, the 9.6% catch rate of stocked fish was unexpectedly low. Consequently, in such recreational fisheries, it could be questionable to stock large E. lucius intended to be harvested as commonly applied for rainbow trout Oncorhynchus mykiss (Walbaum 1792) (Stanković et al ., ). At best, E. lucius may also be stocked after the spawning period to increase their probability of being caught before the spawning season.…”
Section: Results Of the Generalized Linear Model Aimed At Testing Thementioning
confidence: 97%
“…Despite the lack of data about fishing pressure, the 9.6% catch rate of stocked fish was unexpectedly low. Consequently, in such recreational fisheries, it could be questionable to stock large E. lucius intended to be harvested as commonly applied for rainbow trout Oncorhynchus mykiss (Walbaum 1792) (Stanković et al ., ). At best, E. lucius may also be stocked after the spawning period to increase their probability of being caught before the spawning season.…”
Section: Results Of the Generalized Linear Model Aimed At Testing Thementioning
confidence: 97%
“…These sites did not show significant habitat degradation or hydrologic alteration; however, the community was not composed by native trout and gobies or cottids, but rather solely composed by rainbow trout (Oncorhynchus mykiss). This species was previously reported to establish in different areas of Italy (Stanković et al 2015), even if many more populations are known but not yet reported (Milardi, unpublished data), but its interactions with native fish and invertebrates are still largely unexplored. Candiotto et al (2011) hypothesized that rainbow trout could colonize mainly river stretches where no other fish were present.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown large negative effects (i.e. Rainbow trout have been introduced in Slovenia in the early 20th century for recreational purposes and have established numerous self-sustaining populations in Slovenian Adriatic basin (Stanković et al, 2015), threatening the viability of the endangered native salmonid species marble trout Salmo marmoratus Cuvier, 1829. Rainbow trout have been introduced in Slovenia in the early 20th century for recreational purposes and have established numerous self-sustaining populations in Slovenian Adriatic basin (Stanković et al, 2015), threatening the viability of the endangered native salmonid species marble trout Salmo marmoratus Cuvier, 1829.…”
Section: Musseau Et Almentioning
confidence: 99%
“…Marble trout in lower Idrijca coexist with non-native rainbow trout, which were introduced only once in the 1960s and have been established since then, but they are absent in upper Idrijca (Stanković et al, 2015). Marble trout in lower Idrijca coexist with non-native rainbow trout, which were introduced only once in the 1960s and have been established since then, but they are absent in upper Idrijca (Stanković et al, 2015).…”
Section: Musseau Et Almentioning
confidence: 99%